The Phenomenon of Silencing Activists in the Novel Laut Bercerita and Digital Silencing in Indonesia: An Analysis of Gramsci's Hegemony - Nurul Kholifah; Hasan Busri; Sri Wahyuni (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2025)
The silencing of critical voices has evolved from physical repression during the New Order era to the sophisticated mechanisms of digital suppression in contemporary Indonesia. This study aims to reveal the continuity and transformation of silencing practices by analyzing Leila S. Chudori’s novel Laut Bercerita alongside present-day digital suppression phenomena through Antonio Gramsci’s theory of hegemony. Employing a qualitative approach, the research integrated content analysis of the novel and documentation of digital silencing cases collected through literature reviews, close reading, and interactive data analysis methods, involving iterative coding, theme development, and validation across multiple data sources. The findings revealed that Laut Bercerita portrays silencing through coercion and ideological manipulation by the New Order regime, reflected in acts of torture, enforced disappearances, and propaganda. These practices exhibited fundamental similarities to modern digital suppression tactics, such as algorithm manipulation, shadow banning, and doxxing. Viewed through Gramsci's theoretical lens, both eras demonstrated the interplay of coercive force and ideological control to maintain hegemony. The study concludes that despite medium shifts, the silencing mechanisms persist across time. It further recommends the development of counter-hegemonic strategies. Specifically, creating alternative narratives and independent digital spaces that challenge dominant power structures to resist the increasingly complex nature of digital repression.